The relationship between athletes` identity and attitudes toward social contribution among female professional soccer players - Yuko, T. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
Background Established in 2021, the Women`s Empowerment League (WE League) is Japan`s first professional womens soccer league. Its mission is to be "the best in the world" and to "solve social problems" at the same time. Until now, it has been uncommon in Japans athlete development system for athletes to spend time outside of competitions on social contribution activities. Purpose The purpose of this study is to elucidate the characteristics of players who aim to be both "the best in the world" and to "solve social problems," and the reality of their social contribution awareness. Methods Subjects included total of 114 players (age range 18-40) in the WE League. Based on the Athletic Identity Measurement Scale (AIMS) (Brewer and Cornelius, 2001: Hagiwara and Isogai, 2020) sub-scales (social identity, exclusiveness, and negative emotions) and philosophy understanding scores, we conducted hierarchical cluster analysis using the Ward method to classify interpretable clusters. Based upon these clusters, we calculated differences in "environmental changes surrounding professional soccer" and "awareness of social contribution." Results The analysis resulted in the following three clusters: one with high scores on the three AI factors but low scores on philosophical understanding (n=39; competition priority group), one with low scores on all three AI factors and philosophical understanding (n=27; overall low cluster), and one with high scores on social identity and philosophical understanding but average scores on exclusiveness and negative feelings (n=48; philosophy-compatible group). Utilizing these three clusters as factors, we conducted a single-factor variance analysis with no correspondence and found significant main effects for "changes in the environment surrounding professional soccer" (F(2,111)=12.353, p<.05). The scores of the philosophy-compatible group were significantly higher than those of the other two groups (p<.05). Discussion Subjects in the philosophy-compatible group had a higher understanding of off-the-pitch initiatives to raise awareness of social contribution, and were more involved in the games. Sharing social issues among various stakeholders and raising them as issues may deepen the connection with society.